PENGARUH KOMPENSASI, MOTIVASI KERJA, DAN DISIPLIN KERJA TERHADAP KINERJA KARYAWAN PT. SHELTER - Rifky, Oktafianto; Aufa Izzuddin, Baihaqi (Jurnal Bisnis Indonesia, 2021)
This study aims to determine (1) the effect of compensation on the performance ofemployees of PT. Shelter (2) the influence of motivation on employee performance at PT.Shelter (3) the effect of work discipline on employee performance at PT. Shelter.This research method uses quantitative methods. The population in this study wereemployees of PT. Shelter. The sampling technique used Probability sampling by usingstratified random sampling and took 41 respondents. The data analysis technique used ismultiple linear regression analysis.Based on the results of this study that Fcount namely H0 is rejected and H1 is accepted so itcan be concluded that the independent variable is Compensation (X1), work motivation(X2), Work discipline (X3) has a significant influence on the Performance variable (Y) ofPT. Shelter. Compensation tcount results namely H0 are accepted at a significance level of5% so that the conclusion is partially the compensation variable (X1) has a significant effecton Employee Performance (Y). The result of work motivation is that H0 is rejected at the5% significance level so the conclusion is partially the Work Motivation variable (X2) has asignificant influence on Employee Performance (Y). while the results of the WorkDiscipline Tcount that is H0 rejected at the 5% significance level so that the conclusion ispartially the Work Discipline variable (X2) has a significant effect on EmployeePerformance (Y). Keywords: Compensation, Work Motivation, Work Discipline, Employee Performance DOI : https://doi.org/10.33005/jbi.v12i1.2601